Entrepreneurship Development in Somalia. - Hanad, Bashir (2019)
Since the First Industrial Revolution entrepreneurship has frequently enhanced a subject of interest for various stakeholders (e.g. governments, firms, businessmen, researchers, and scientists). The importance of entrepreneurship over the socio-economic life are numerous and great such as job creation, social composition, innovation, technological development, wealth conception, and economic growth and improvement (Sorin-george & Papuc, 2017) This paper gave an overview of current entrepreneurship in Somalia also the paper studies major risks, improvements concerning to the entrepreneurship of Somalia.